2006
DOI: 10.1038/nature05364
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a carbohydrate transporter from symbiotic glomeromycotan fungi

Abstract: The symbiotic relationships between mycorrhizal fungi and plants have an enormous impact on terrestrial ecosystems. Most common are the arbuscular mycorrhizas, formed by fungi belonging to the phylum Glomeromycota. Arbuscular mycorrhizal fungi facilitate the uptake of soil nutrients by plants and in exchange obtain carbohydrates, thus representing a large sink for atmospheric plant-fixed CO(2). However, how carbohydrates are transported through the symbiotic interface is still unknown. Here we report the chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 19 publications
1
104
1
2
Order By: Relevance
“…The plant cell wall in the interface space of arbuscular mycorrhizae was shown to be amorphous, very thin, and containing sugar mainly as glucose, mannose, galactose and xylose (Bonfante 2001). It was speculated, therefore, that at least a portion of the monosaccharides could be liberated from plant extracellular polysaccharides and taken up by arbuscular mycorrhizal fungi (AMF) (Schu¨ßler et al 2006). To illustrate the location and the forms of sugar and Pi transported at the arbuscule-cortical cell interface in the AM symbiosis, we incorporated those elucidated in recent publications in Fig.…”
Section: Sugar Fluxes At the Arbuscule á Cortical Cell Interface In Amentioning
confidence: 99%
See 3 more Smart Citations
“…The plant cell wall in the interface space of arbuscular mycorrhizae was shown to be amorphous, very thin, and containing sugar mainly as glucose, mannose, galactose and xylose (Bonfante 2001). It was speculated, therefore, that at least a portion of the monosaccharides could be liberated from plant extracellular polysaccharides and taken up by arbuscular mycorrhizal fungi (AMF) (Schu¨ßler et al 2006). To illustrate the location and the forms of sugar and Pi transported at the arbuscule-cortical cell interface in the AM symbiosis, we incorporated those elucidated in recent publications in Fig.…”
Section: Sugar Fluxes At the Arbuscule á Cortical Cell Interface In Amentioning
confidence: 99%
“…Isotopic labeling and radio-respirometry (Solaiman and Saito 1997) have been used to show that sucrose allocated to the symbiotic interfaces through the apoplast and symplast pathways (Hause and Fester 2005;Bu¨cking and Shachar-Hill 2004) is hydrolyzed to glucose and fructose by a cellwall-bound invertase, and these monosaccharides are taken up by the fungi (Schubert et al 2004). Schu¨ßler et al (2006) demonstrated recently that there might be sugars other than glucose and fructose that are transported at the arbuscule-cortical cell interfaces. Glomeromycotan monosaccharide transporter (GpMST1) functions as a proton co-transporter in transporting monosaccharides, with rates in the following order: glucose mannose galactose fructose (Schu¨ßler et al 2006).…”
Section: Sugar Fluxes At the Arbuscule á Cortical Cell Interface In Amentioning
confidence: 99%
See 2 more Smart Citations
“…Electrophysiological studies showed its substrate specificity, whereas cytological analysis showed that it is very specifically localised at the haustorial plasma membrane. Similarly, the mycorrhizal fungus Geosiphon pyriformis, which forms a symbiotic relationship with plant roots allowing them to acquire nutrients more efficiently from soil, possesses a novel hexose transporter with highest affinity for glucose (followed by mannose, galactose, and fructose), which may be involved in the fungus-root cell mutualistic symbiosis that is of such importance to plant growth in diverse terrestrial ecosystems [20]. However, the role of these transporters in each respective plant-fungal interaction could not be determined by gene functional analysis because both U. fabae and G. pyriformis are obligate symbionts, which cannot be cultured away from their plant hosts, so the significance of these Figure 1.…”
mentioning
confidence: 99%